Evidence for transovarial transmission of tick-borne rickettsiae circulating in Northern Mongolia. - Thomas C Moore; Laura A Pulscher; Luke Caddell; Michael E von Fricken; Benjamin D Anderson; Battsetseg Gonchigoo; Gregory C Gray (Public Library of Science (PLoS), 2018)
Transstadial transmission of tick-borne rickettsiae has been well documented. Few studies, however, have evaluated the role of transovarial transmission of tick-borne rickettsiae, particularly in nature within the host-vector ecosystem. This cross-sectional study aimed to understand the role of transovarial transmission of tick-borne rickettsiae among feeding ticks at different life stages. Tick eggs laid by engorged wild-caught adult female ticks were pooled and tested for Rickettsia spp. and Anaplasma/Ehrlichia spp. using molecular techniques, while adult fed ticks were tested individually. Additionally, larval and nymphal ticks were collected in the wild from small mammals, pooled and tested for Rickettsia spp. and Anaplasma/Ehrlichia spp. There were 38 fed adult and 618 larvae/nymphs (60 pools total) Dermacentor spp. ticks collected from livestock and rodents. All individual adult ticks and tick pools were positive for Rickettsia spp. While none of the larvae/nymphs were positive for Anaplasma/Ehrlichia spp., two adult fed ticks were positive. Rickettsia spp. DNA was detected in 91% (30/33) of the pooled eggs tested, and one pool of eggs tested positive for Anaplasma/Ehrlichia spp. Sequencing data revealed Rickettsia spp. shared ≥99% identity with R. raoultii ompA. Anaplasma/Ehrlichia spp. shared ≥89% identity with A. ovis 16S ribosomal RNA. This study identified potential transovarial transmission of Rickettsia spp. and Anaplasma spp. among D. nuttalli ticks. Additional studies are needed to further assess the proportion of transovarial transmission occurring in nature to better understand the burden and disease ecology of tick-borne rickettsiae in Mongolia.